Pengaruh Brand Personality dan Brand Experience Terhadap Emotional Brand Attachment Pada Merek Vespa - Resnu Dwi Andika; Guntur Freddy Prisanto (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2019)
With a background in consumer attitudes toward brands, researchers analyze the behavior of modern consumers who no longer only buy products and services, but they buy extraordinary experiences and emotional experiences that arise when buying and selling transactions. If the experience that consumers have is positive, it is predicted that consumers will be happy to repurchase the brand. This research was conducted by distributing questionnaires to Vespa riders who are members of the classic Vespa and Vespa Modern communities. The sampling technique by census. The results of this study obtained that the brand personality variable has a smaller value than the brand experience. This shows that the respondent's experience on Vespa brands is not only when driving, but also changes their behavior and mindset towards Vespa brands. The implication of the results of this study is the brand experience in riding a Vespa has a very strong contribution in the effort to form emotional attachments. To increase the emotional attachment to the brand, Vespa must evaluate the existence of its authorized dealers according to the respondents less spread. Service 3S or better known as an abbreviation of Sales, Spare Parts & Service is one of the key factors that determine the closeness of consumers with producers/Vespa.